2020
DOI: 10.3390/ijerph17176366
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: Age-Related Differences in Measures of Stress, Anxiety and Depression in Canada

Abstract: Background: The spread of COVID-19 along with strict public health measures have resulted in unintended adverse effects, including greater levels of distress, anxiety, and depression. This study examined relative presentations of these psychopathologies in different age groups in a Canadian cohort during the COVID-19 pandemic. Methodology: Participants were subscribers to the Text4Hope program, developed to support Albertans during the COVID-19 pandemic. A survey link was used to gather demographic information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
184
14
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(275 citation statements)
references
References 27 publications
36
184
14
13
Order By: Relevance
“…We aimed to identify risk factors for anxiety, depression and PTSD in relation to the SARS-CoV-2 epidemic. We did not find some of the risk factors previously reported in the literature, such as female sex, young age, being a nurse or a “frontline worker” or belonging to non-medical staff [1] , [2] , [3] , [6] , [16] , [19] , [20] , [23] , [24] , [25] , [26] , [27] , [28] . This finding might be explained, with regards to age and sex, by the proportion of males and people younger than 25 years in our population.…”
Section: Discussioncontrasting
confidence: 86%
“…We aimed to identify risk factors for anxiety, depression and PTSD in relation to the SARS-CoV-2 epidemic. We did not find some of the risk factors previously reported in the literature, such as female sex, young age, being a nurse or a “frontline worker” or belonging to non-medical staff [1] , [2] , [3] , [6] , [16] , [19] , [20] , [23] , [24] , [25] , [26] , [27] , [28] . This finding might be explained, with regards to age and sex, by the proportion of males and people younger than 25 years in our population.…”
Section: Discussioncontrasting
confidence: 86%
“…And the result showed 30.2% residents in Wuhan had moderate to severe anxiety, which is much higher than our result (21.2%) [39]. A nationwide study included 1210 general public from 194 cities in China conducted between January 31 to 1% residents in Canada have moderate to severe depression and anxiety which is higher than our result [40]. Also, a Spanish study of psychological symptoms during the two-stage lockdown in response to COVID-19 showed that 26.9% and 27.5% of participants had symptoms of anxiety and depression which is also higher than our results and psychological symptoms increase as lockdown time increases [41].…”
Section: Plos Onecontrasting
confidence: 86%
“…Higher scores represent greater self-reported PTSD. The total score of the scale was interpreted as follows: normal (17-37), mild (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and (50-85) PTSD. A cutoff score of 50 used to detect the PTSD has demonstrated good sensitivity of 0.82 and specificity of 0.86 [30].…”
Section: Study Instrumentsmentioning
confidence: 99%
“…The available research data, mainly on the general population, seem to be incoherent as to the role of age in experiencing high levels of stress and anxiety during the pandemic. Some survey-studies suggested higher levels of anxiety were found in younger responders [ 29 ], whereas others reported the highest anxiety levels in elderly people [ 25 ].…”
Section: Discussionmentioning
confidence: 99%